Discovery of the most ancient member of family Tanyderidae (Diptera) from the Lower Jurassic (Sinemurian) of England - Skibińska, Kornelia; Krzemiński, Wiesław; Coram, Robert A. (Zootaxa, 2014)
Nannotanyderus oliviae sp. nov. from the Lower Jurassic (Sinemurian) of England, the oldest representative of family Tanyderidae, is described and illustrated.